Remoção de carga orgânica de efluente hospitalar por reator de leito móvel com biofilme, em escala de bancada - Soares, Ana Marceli (2014)
Moving bed biofilm reactors (MBBR) were developed in the end of last century in Norway, and have excelled over other processes, and incorporate great features of biological wastewater treatment. In the process, the microorganisms grow attached to carriers, forming biofilm. In this work was studied the efficiencies of MBBR in the hospital sewage treatment, with the aim of removing organic load, Total Kjeldahl Nitrogen (TKN) and total phosphorus. In the LabCAmb/UFSM, the MBBR was operated to treat hospital sewage under aerobic conditions, with useful volume of 4.1 L, filling ratio of 60%, flow rate of 1.0 L.h-1, and hydraulic detention time of 4.1 h. The volumetric organic load (VOC) of the influent varied widely, were obtained values of between 0.703 and 2.752 Kg BOD5.m-3.d-1 (1.02 a 7.53 Kg COD.m-3.d-1), resulting in an average to VOC of 1.55 Kg BOD5.m-3.d-1 (2.99 Kg COD.m-3.d-1). The MBBR showed good performance, with average to removal efficiencies of VOCs in BOD5 and COD of 76.36 and 69.54%, respectively. The average TKN removal efficiency was 46.85%, removal due to biological synthesis and probably reactions of simultaneous nitrification/denitrification. For total phosphorus was obtained an average to removal efficiency of 46.45%, due to cell accumulation.